THE EFFECT OF MIGRANT WORKER REMITTANCES, UNEMPLOYMENT, AND ECONOMIC GROWTH ON POVERTY IN INDONESIA: VECM ANALYSIS FROM AN ISLAMIC ECONOMIC PERSPECTIVE (2010-2024) - Zuliandika, Muhammad Rizki; Anggraeni, Erike; Susanto, Is (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2025)
Poverty in Indonesia remains become challenge although trend its decline positive. Utilization remittances worker migrant not optimal, level unemployment fluctuating, and growth economy no always inclusive. Research this aim for analyze influence remittances worker migrants, unemployment, and growth economy to poverty in Indonesia in perspective economy Islam. The data used is sequential data time per semester for 2010-2024 obtained from the Central Statistics Agency, Bank Indonesia, BP2MI and other relevant literature, analyzed use approach Vector Error Correction Model (VECM) with help device EViews 12 software. Research results show that in term length, remittances and growth economy own influence negative and significant to poverty, while level unemployment no influential significant. On the other hand, in term short, unemployment and growth economy influential significant, whereas remittances no. Findings this confirm that alleviation poverty need growth inclusive and equitable economy, management​ remittances in a way productive, as well as creation field work dignified in accordance principle economy Islam. In general academic, findings this enrich literature empirically. In practical, to be base policy alleviation poverty based Islamic values.